Caracterização físico-química, de minerais e atendimento à legislação de queijos produzidos e comercializados no estado da Paraíba, Brasil - Oliveira, Tayanna Bernardo (2016)
Recent advances in Nutrition Science have already highlighted the contribution of cheese to nutrition and health because of the amount of nutrients available in it. Cheeses have a long history in the human diet, and have long represented the primary concentrated form of milk, with the benefit of prolonged shelf life. Due to the increase in the consumption of cheeses in Brazil, its production increased, increasing also the demand of the competent organs as to the quality of these products. Growing societal demand for reliable product information requires government and industry efforts to effectively implement food labeling. The objective of this study was to evaluate the physico-chemical characteristics, composition of the main minerals, as well as the compliance with the legislation of different types of cheeses produced and marketed in the State of Paraíba. Initially, a survey was made of the commercial types of cheese from the State and from these data were selected 9 brands of bovine milk rennet cheese, two brands of goat milk rennet cheese, seven fresh ricotta cheese, five butter cheese, Two fresh mines and one standard Minas Gerais cheese brand, which had a state or federal inspection seal purchased from the local commerce of the cities of João Pessoa, Campina Grande and Guarabira - Paraíba. The determination of the minerals was by ICP - OES, the means found were for calcium, 932.03 mg / 100 g in goat milk rennet cheese, phosphorus 596.47 mg / 100 g in fresh mines, magnesium 190.63 mg / 100 g in goat milk rennet cheese and zinc 4.34 mg / 100 g in the fresh minas cheese. The commercial cheeses minerals from the State of Paraíba can be considered as good sources of calcium, phosphorus, magnesium and zinc, noting that cheeses presented high sodium content (706.66 mg / 100 g in butter cheese) and these high values may Health. The composition of the cheese labels when compared to the physical-chemical analyzes was inadequate according to the Brazilian legislation in force in 44% of cheeses of bovine milk rennet, 50% of cheeses of goat milk rennet, 71% of ricotas and 40 % Of butter cheeses. The hygienic-sanitary quality analyzes indicated the presence of coliforms at 45 ° C in 17.95% of the samples, E. coli in 11.54% and Staphylococcus coagulase positive in 1.28% of the samples, Salmonella spp. Absent in the samples. The different parameters analyzed demonstrate the need to standardize the processing of the cheeses produced and marketed in the State and indicate that the consumption of these cheeses can pose health risks.